Optimization of the control process in residential buildings using technological tools - Prat, Joaquin (2020)
Many construction companies worldwide continue to implement different methodologies to optimize time and improve management in the execution of works; however, a lack of control in projects continues to be observed. For this reason, one of the most common problems currently is the incompletion of scheduled work. Due to this, it is necessary to keep better control of the projects at the execution stage so that the contractor can optimally, quickly, and easily manage the progress of all the specialties involved. In this sense, this research develops the use of the Plan Grid Application for data collection in the field and the Power Bi software for the automatic processing and information visualization through a management dashboard where indicators are shown to reflect the progress and actual performance of the activities as well as the main non-compliance causes, which leads to optimize the control process and the time spent by its administrators to carry out this management.